APPLICATION OF VALUE-BASED PRICING IN INDUSTRIAL SECTOR - Nieminen, Teppo (My University, 2016)
The traditional cost- and competition-based pricing approaches are dominating in the industrial sector. Meanwhile, fierce competition and increasing pressures on prices have drawn attention to find alternative pricing strategies and approaches. Pricing based on a customer desired value is on the rise and pricing practitioners and marketing scholars praise its superiority in increasing profitability and competitive advantage. However, the transition towards value-based pricing seems to be route fraught with obstacles. As pricing is connected to management accounting system, which is said to constitute the rules and routines of an organization, it requires conquering the internal change resistance and changing the prevailing institution around the old pricing strategy. Furthermore, it requires involvement by top management and strong leadership in delivering the change. Eventually, comprehensive implementation of value-based pricing requires understanding the value customers perceive and influencing it through value quantification and communication, and finally capturing a share of the created value. The purpose of this thesis is to study the factors that affect the application of value-based pricing in a case company organization within the industrial sector. Variables of work experience, position and education are used with measures of motivation and confidence, presence of institution and the importance of management sponsorship to analyse whether they have diverging affect towards change in pricing strategy (value-based pricing). The application of value-based pricing in the case company is analysed from the viewpoint of selling to shipyards (as a sub-supplier) and ship owners (as a main supplier). The results of this study do not indicate that the defined variables regarding the change resistance and importance of management sponsorship would have impact to the selected measures. However, the presence and effect of (old) institution was admitted. On the functionality of value-based pricing in industrial sector; the results were somewhat consistent with the previous findings, indicating the challenges in its application.
Keywords: value-based pricing; customer-perceived value; management accounting system change; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Laskentatoimen ja tilintarkastuksen maisteriohjelma|en=Master's Programme in Accounting and Auditing|